Prenatal Exposure to Gossypol Impairs Corticogenesis of Mouse - Zhu, Xiaoyan (Front Neurosci, 2020)
Gossypol is a yellow polyphenolic compounds extracted from roots, stems and seeds of cotton plants. Excessive intake of gossypol induces severe pathological signs of toxicity in livestock and wildlife. Currently, gossypol has received widespread attention for its toxic effects on the reproductive system. However, reports of the effects of gossypol during corticogenesis and the development of the mouse cerebral cortex are unavailable. In the present study, gossypol was orally administrated at a dose of 0, 20, and 50 mg/kg body weight/day to pregnant mice from embryonic day 6.5 to the time of sample collection. We used in utero electroporation and immunofluorescence to demonstrate that gossypol impaired cortical neuronal migration. Furthermore, labeling with 5-bromo-2-deoxyuridine and western blot analysis revealed that gossypol disturbed the balance between proliferation and differentiation of neural progenitors, inhibited neural progenitor cell proliferation, neuronal differentiation, and maturation. Additionally, cortical progenitor apoptotic cell death increased in the developing gossypol-treated cortex, which was associated with NF-κB and MAPK pathways. In conclusion, our findings indicate that gossypol exposure disrupted neurogenesis in the developing neocortex, suggesting the potentially harmful impact of gossypol on the cerebral cortex development of humans and livestock.